The political career of Saul Solomon, Member of the Cape Legislative Assembly from 1854 to 1883 - Drus, Ethel (Department of Historical Studies, 2016)
Saul Solomon was born in 1817 and died in 1892. He was never a member of the Legislative Council, so that his political career can be said to have begun in 1854, when he was returned to the first House of Assembly as one of the four members representing Capetown. He held his seat with a break of only one year, in 1869, until 1883, when illness oompelled him to retire. To my mind, prior to 1854, he was but an 'amateur' politician, using the word in no depreciatory sense,and I therefore propose to concentrate most of my attention on his parliamentary career.